Potret Kucing sebagai Hasil Fantasi Patriarki dari Puisi “Ngiau” Karya Sutardji Calzoum Bachri - Mukafi, Muhammad Hamdan; Wahyuningsih, Triyanti (Fakultas Ilmu Budaya Universitas Diponegoro, 2020)
Literary works are able to evolve their meaning in relation to the presence of an illustration embedded in them. Like the poem